2005
DOI: 10.1007/s00020-005-1416-y
|View full text |Cite
|
Sign up to set email alerts
|

Admissibility of Unbounded Operators and Wellposedness of Linear Systems in Banach Spaces

Abstract: We study linear systems, described by operators A, B, C for which the state space X is a Banach space. We suppose that −A generates a bounded analytic semigroup and give conditions for admissibility of B and C corresponding to those in G. Weiss' conjecture. The crucial assumptions on A are boundedness of an H ∞ -calculus or suitable square function estimates, allowing to use techniques recently developed by N. Kalton and L. Weis. For observation spaces Y or control spaces U that are not Hilbert spaces we are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…See [29] for information on this space. We note that a version of the following Lemma is also in [15,Proposition 3.19], where it is instead assumed that Y has so-called property (α). Moreover, in [15,Remark 5.3 and Proof of Proposition 3.19] it is claimed that this assumption can be relaxed to non-trivial cotype, which is weaker than our assumption below.…”
Section: (52)mentioning
confidence: 99%
See 1 more Smart Citation
“…See [29] for information on this space. We note that a version of the following Lemma is also in [15,Proposition 3.19], where it is instead assumed that Y has so-called property (α). Moreover, in [15,Remark 5.3 and Proof of Proposition 3.19] it is claimed that this assumption can be relaxed to non-trivial cotype, which is weaker than our assumption below.…”
Section: (52)mentioning
confidence: 99%
“…We note that a version of the following Lemma is also in [15,Proposition 3.19], where it is instead assumed that Y has so-called property (α). Moreover, in [15,Remark 5.3 and Proof of Proposition 3.19] it is claimed that this assumption can be relaxed to non-trivial cotype, which is weaker than our assumption below. However, there seems to be a small confusion there: in [15,Remark 5.3] it is observed that non-trivial cotype suffices, thanks to a result in [17], if (a certain Hilbert space) H 1 = C, whereas in [15,Proposition 3.19] and the following lemma one has the dual situation: H 1 = H is a general Hilbert space and H 2 = C. Indeed one could deduce the following lemma by a standard duality argument from the result in [17], but since a self-contained argument is only slightly longer, we provide it for completeness: .…”
Section: (52)mentioning
confidence: 99%
“…[6,Section 6], [7,Proposition 3.3 and Theorem 4.12], [13], [16,Section 3], [19,Section 4], [21,Chapter 2]). However, it seems they are of a different nature and cannot be used to prove Theorems 1.1, 3.10 and Corollary 3.14.…”
Section: Introductionmentioning
confidence: 99%
“…However, unfortunately, it is hard to test the admissibility, not to mention the well-posedness and regularity of an infinite-dimensional linear system with unbounded control and observation. There are many papers devoted to discussion on the admissibility of control and observation operators, most of which are interested in proving or disproving Weiss' conjecture (see, e.g., [6,[12][13][14][15]25,29,34,35]). Here, we mention an important work due to Zwart [35]; he proved that the Weiss conjecture almost holds in Hilbert spaces and in the case that p = 2.…”
Section: Introductionmentioning
confidence: 99%